A Juridical Analysis of the Comparison of Legality Principle in the Indonesian Criminal Code (WvS) and the Draft of New Indonesian Criminal Code (National Criminal Code) - Wirabakti, Muhammad Zakaria; Rochaeti, Nur (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The principle of legality in the current Indonesian Criminal Code (WvS) is a principle of formal legality. This principle is influenced by the positivist school which only considers law as written legislation/regulations. In contrast to the principle of legality in the current Indonesian Criminal Code, the principle of legality in the Draft of New Indonesian Criminal Code (Indonesia’s Original Criminal Code), or called National Criminal Code, is known as the principle of formal legality and the principle of material legality. The combination of these two principles does not only consider law as a written legislation/regulation but also provides space for customary law or law that exists in society as a basis for proper punishment for a crime as long as the crime has no similarities or is not regulated in the existing laws. This study was normative research, aiming at determining the juridical differences in the legality principle in the current Indonesian Criminal Code (WvS) and the Draft of New Indonesian Criminal Code (National Criminal Code). In this study, the researchers applied a qualitative analysis method.